Yooddooddoom: A narrative exploration of the camp and the sacred place, daily life, images, arranged stones and Lalai Beings. Issue 3 (December 2016) - Oobagooma, Janet; Doohan, Kim; Umbagai, Leah; Porr, Martin
Abstract : This paper seeks to explore 'taking a narrative approach' as a research methodology in the wider context of gaining a situated understanding of the ethnographic context of the Indigenous rock art of the northwest Kimberley. Its phenomenological approach is based on the recollections of a senior Woddordda woman when she was a child living a largely subsistence existence with her older kin. This glimpse into the ways these Indigenous people engaged with their rock art and interpreted it in their daily lives is a counterpoint to the predominantly archaeological study of this acclaimed tradition. The original presentation was located in Janet Oobagooma's narration of her experiences and knowledge working with Kim Doohan whilst at the location along with the selection of images presented here. This was later followed by collaboration and negotiations with Martin Porr and Mrs Oobagooma's granddaughter, Leah Umbagai. This paper is, in essence, a narrative of narrative-based research methods and subsequent findings.